Studi Musuh Alami (Spodoptera Exigua Hbn) pada Agroekosistem Tanaman Bawang Merah - Nusyirwan, Nusyirwan (Politeknik Negeri Lampung., 2013)
Study natural enemy Spodoptera Exigua was condetd on onion agro ekosistem in farmers field Sungai Nanam Alahan Panjang West Sumatera from August to October 2009. Methode of the Riset was with sampling with out sprayed and sprayed insecticide of served with each week from plant age 20 days in one planting season. In land with out application insecticide and application insecticide there were no eggs and larva were paraside. The Natural enemy in land area with aut application insecticide and application lend. The bigger from dominand were from family Braconidae ordo Hymenoptera, followed by family Aracnidae ordo aracnida, family Forficulidae ordo Demaptera, family Coccinelidae Ordo Coleoptera, family Braconidae Ordo Hymenoptera dan family Tachinidae Ordo Diptera